Langman's medical embryology - Sadler, T. W. (Thomas W.) .) (Wolters Kluwer Health/Lippincott Williams & Wilkins, 2019)
Reaching far beyond the 9 months of gestation and the first year of life, embryonic development has ramifications for health throughout the human lifespan. Improved reproductive outcomes and healthier babies, while the specific goals of obstetricians, are areas of clinical relevance for all healthcare professionals. This book facilitates understanding of the molecular, cellular, and structural factors contributing to human development. With its trademark approach combining economy of text with exceptional artwork, this revised 12th edition clearly and effectively presents embryology in a clinical context for students of medicine and the health professions. Enhancements to the 12th edition include: An all-new introduction that covers the history and clinical relevance of embryology; Current research and detailed coverage of molecular regulation and signaling, the cardiovascular and digestive system, and the limbs; and each chapter includes overview figures that provide a visual introduction to the material. -- from Back Cover
Includes index
Keywords: Abnormalities, Human; Embryonic Development; Congenital Abnormalities; Embryology